Local water source variation and experimental Chicha de Maíz brewing: Implications for interpreting human hydroxyapatite δ18O values in the Andes. (December 2015) - Gagnon, Celeste Marie; Andrus, C. Fred T.; Ida, Jennifer; Richardson, Nicholas
Abstract: Oxygen isotope data (expressed as δ 18 O values) recovered from human skeletal remains have been the central focus of a number of archeological analyses tracking human migration. However, in the Andes the use of oxygen isotopes to investigate residential mobility is subject to two issues addressed in this study: 1) local variation in water sources and 2) pre-consumption processing of water. To explore these factors we sampled a wide variety of water sources in the Moche watershed of north coastal Peru and experimentally and ethnographically produced chicha de maíz, a traditional brewed beverage. Our data indicate an unexpected spatial pattern in Moche valley water source δ 18 O values, and identify springs as an important influence on river water. Using chicha de maíz as an example of pre-consumption processing of water, we find that brewed beverages may impact human δ 18 O values. Together these data indicate that in the Andes the consumption of chicha de maíz has the potential to swamp spatial variation in water source δ 18 O values. Therefore, we cannot assume that the identification of different δ 18 O values in the remains of Andean groups necessarily indicates the presence of migrants. Highlights: Moche valley water sources are characterized by decreasing δ 18 O values with decreasing altitude. Chicha is substantially enriched in heavy oxygen, so its consumption can affect human δ 18 O values. Smaller boil vessels will result in chichas with more positive δ 18 O values than larger boil vessels. Variation in recipe leads to variation in δ 18 O values with less viscous chichas being more enriched.